Shaping self-efficacy in online mathematics: A comparative study by gender and semester level - Nurhayati, Suci; Noviyanti, Mery; Mohamad, Liana (Jurnal Elemen, 2025)
Self-efficacy plays an important role in online mathematics learning, especially because the process demands a high level of independence and self-regulation. However, few studies have explored how sources of self-efficacy may differ based on gender and academic stage in the context of distance education. This study aimed to examine whether there are significant differences across five sources of self-efficacy–mastery experience, vicarious experience, social persuasion, physiological state, and belief–based on students’ gender and academic semester. A total of 104 students from the Mathematics Education program at Universitas Terbuka participated in this study. As the data did not meet the normality assumptions, the Mann–Whitney U and Kruskal–Wallis tests were used. The results showed no significant differences between male and female students across any of the self-efficacy dimensions. However, the academic semester revealed significant differences in two dimensions: social persuasion and belief, with middle-semester students scoring the highest. This implies that self-efficacy support strategies should be tailored to students' academic stages. Those in early semesters may benefit more from peer modelling and encouragement, while those nearing graduation may need more support to manage academic stress. Future studies should involve more diverse samples to validate these results.